Bradycardia and hypothermia complicating azithromycin treatment - Benn, K.; Salman, S.; Page-Sharp, Madhu; Davis, T.; Buttery, J. (2017)
Â© Am J Case Rep, 2017. Objective: Unusual or unexpected effect of treatment Background: Azithromycin is a macrolide antibiotic widely used to treat respiratory, urogenital, and other infections. Gastrointestinal upset, headache, and dizziness are common adverse effects, and prolongation of the rate-corrected electrocardiographic QT interval and malignant arrhythmias have been reported. There are rare reports of bradycardia and hypothermia but not in the same patient. Case Report: A 4-year-old boy given intravenous azithromycin as part of treatment for febrile neutropenia complicating leukemia chemotherapy developed hypothermia (rectal temperature 35.2Â°C) and bradycardia (65 beats/minute) after the second dose, which resolved over several days post-treatment, consistent with persistence of high tissue azithromycin concentrations relative to those in plasma. A sigmoid E max pharmacokinetic/pharmacodynamic model suggested a maximal azithromycin-associated reduction in heart rate of 23 beats/minute. Monitoring for these potential adverse effects should facilitate appropriate supportive care in similar cases. Conclusions: Recommended azithromycin doses can cause at least moderate bradycardia and hypothermia in vulnerable pediatric patients, adverse effects that should prompt appropriate monitoring and which may take many days to resolve.